2018
DOI: 10.1093/ibd/izy281
|View full text |Cite
|
Sign up to set email alerts
|

Bacteroides thetaiotaomicronAmeliorates Colon Inflammation in Preclinical Models of Crohn’s Disease

Abstract: B. thetaiotaomicron displays strong efficacy in preclinical models of IBD and protects against weight loss, histopathological changes in the colon and inflammatory markers. These data indicate that the live strain or its products may be a novel alternative to current treatment options for Crohn's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
116
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(122 citation statements)
references
References 58 publications
5
116
0
1
Order By: Relevance
“…The importance of regulatory IL-10 to the healthy response of DC to Bt OMVs is congruent with observations in mice showing that Bt is colitogenic in dnKO mice lacking IL-10 and TGFb-signalling pathways 10,24 . Conversely, a strain of Bt different to that used in our study was shown to protect otherwise susceptible IL-10R-deficient mice or dextran sodium sulfate-treated mice and rats from developing colitis 11 . These discrepancies support the proposal that Bt protective functions are, at least in mice, not limited to IL-10-related pathways and may be dependent on environmental, bacterial strain-and host-specific factors 69 .…”
Section: Discussionmentioning
confidence: 58%
“…The importance of regulatory IL-10 to the healthy response of DC to Bt OMVs is congruent with observations in mice showing that Bt is colitogenic in dnKO mice lacking IL-10 and TGFb-signalling pathways 10,24 . Conversely, a strain of Bt different to that used in our study was shown to protect otherwise susceptible IL-10R-deficient mice or dextran sodium sulfate-treated mice and rats from developing colitis 11 . These discrepancies support the proposal that Bt protective functions are, at least in mice, not limited to IL-10-related pathways and may be dependent on environmental, bacterial strain-and host-specific factors 69 .…”
Section: Discussionmentioning
confidence: 58%
“…Moreover, MV also significantly increased the abundance of B. ovatus in our study (Figure G). A closely related species, B. thetaiotaomicron , has been shown to ameliorate colon inflammation in two different IBD models including DSS model . Cumulatively, evidence suggests that the metabolites of MV metabolism are conducive to host health by enhancing growth of beneficial bacteria in the gut …”
Section: Discussionmentioning
confidence: 99%
“…Bacteroides thetaiotaomicron is an acetate producer that promotes goblet cell differentiation and mucus production, ultimately providing protection against intestinal inflammation by strengthening the gut barrier (89). Recently, additional studies suggested B. thetaiotaomicron colonization demonstrated therapeutic properties in preclinical models of CD (90), although separate studies showed that B. thetaiotaomicron can be pathogenic in patients with certain genetic susceptibilities (75,91). Finally, alterations to bacterial colonization can lead to downstream metabolic or indirect effects on other bacteria.…”
Section: Inflammatory Bowel Diseasementioning
confidence: 99%